2007
DOI: 10.1364/oe.15.014171
|View full text |Cite
|
Sign up to set email alerts
|

Linear and nonlinear optical properties of Hafnium-doped lithium-niobate crystals

Abstract: Measurements of birefringence, second-harmonic phase-matching conditions, and nonlinear coefficient d(31) are performed for a set of Hafnium-doped congruent lithium niobate (Hf:cLN) crystals as functions of dopant concentration. The data highlight that the threshold concentration, above which there is a change in the Hf incorporation mechanism, is slightly above 2mol% and that, up to this value of concentration, the efficiency of nonlinear processes is not affected by the dopant insertion. Combining these resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
18
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(19 citation statements)
references
References 17 publications
1
18
0
Order By: Relevance
“…Meanwhile, the control of photorefraction, i.e., saturated diffraction efficiency, response time, etc., is one of the most important research fields. The incorporation of transition metal ions, such as Fe, Cu, and Mn, can enhance the photorefractive properties of LN crystals [11][12][13], while Mg, In, Zr, and Hf ions would increase the optical damage resistance of LN crystals [14][15][16]. Recently, Tian et al reported that hexavalent Mo 6+ doping can tremendously enhance the photorefractive properties of LN crystals [17].…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, the control of photorefraction, i.e., saturated diffraction efficiency, response time, etc., is one of the most important research fields. The incorporation of transition metal ions, such as Fe, Cu, and Mn, can enhance the photorefractive properties of LN crystals [11][12][13], while Mg, In, Zr, and Hf ions would increase the optical damage resistance of LN crystals [14][15][16]. Recently, Tian et al reported that hexavalent Mo 6+ doping can tremendously enhance the photorefractive properties of LN crystals [17].…”
Section: Introductionmentioning
confidence: 99%
“…A problem remains with this dopant owing to difficulties to grow large high optical quality MgO doped LN crystals. Recently, a set of tetravalent impurity ions (Hf 4+ , Sn 4+ , Zr 4+ ) as new ODR ions were checked [7][8][9][10][11]. It was shown that for these ions, the concentration threshold for ODR can be strongly reduced.…”
Section: Introductionmentioning
confidence: 99%
“…Thanks to high nonlinear optical parameters the waveguide frequency conversion devices based on second harmonic generation, sum and difference frequencies, as well as parametric light generators, infrared (IR) range lasers were realized [2]. Lithium niobate is characterized by nonstoichiometric composition with a high concentration of internal defects which can be compensated with the addition of foreign impurities such as Mg, Zn, In, Sc that increase the stability of the crystal to laser irradiation [3]. Nonlinear optical properties of pure and doped with MgO till 5% crystals of lithium niobate today are well understood [4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%